INNOVATIVE BEHAVIOR THROUGH A COLLABORATIVE AND PARTICIPATORY APPROACH IN STRENGTHENING ORGANIZATIONAL PERFORMANCE AND SUSTAINABLE DEVELOPMENT - Zahera Mega Utama; Abdul Wahab Samad (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Innovative behavior has become one of the most important organizational capabilities in responding to globalization, digital transformation, environmental uncertainty, and increasing institutional competition. Modern organizations require employees who are not only capable of performing routine tasks but are also able to generate ideas, implement improvements, and contribute to organizational transformation. This article examines innovative behavior through collaborative and participatory organizational approaches in strengthening organizational performance and sustainable development. The study adopts a qualitative descriptive approach using literature review and conceptual analysis methods. The discussion focuses on innovative behavior, organizational culture, leadership support, employee participation, organizational learning, and sustainable organizational development. The findings indicate that collaborative and participatory organizational environments significantly influence employees’ innovative behavior by strengthening communication openness, teamwork, organizational trust, and creativity. Leadership styles that encourage participation, empowerment, and organizational learning positively affect employees’ willingness to develop and implement innovation. Furthermore, innovative behavior contributes significantly to organizational effectiveness, public service quality, employee performance, and sustainable development objectives. The study concludes that organizations that successfully develop collaborative, adaptive, and innovation-oriented environments are better prepared to achieve long-term organizational sustainability and competitiveness.